Question

Mathematics

Hallan:

See Answers

Best Answer

Answer:

Solution: We can simplify the expression on the left by canceling out common factors of the numerator and denominator.

Therefore, we have . Solving for , we get:

Finally, substituting into the original expression and simplifying, we get:

\begin{align*}

\frac{(b + d)c}{a} &= \frac{b + d}{a} \cdot c \\

&= \frac{b + d}{\frac{3}{x

&= (b + d) \cdot \frac{x

&= \frac{bx

Solution: We can simplify the expression on the left by canceling out common factors of the numerator and denominator.

Therefore, we have

Finally, substituting

\begin{align*}

\frac{(b + d)c}{a} &= \frac{b + d}{a} \cdot c \\

&= \frac{b + d}{\frac{3}{x

^{{2}y}{6}z^{2}}} \cdot c \\&= (b + d) \cdot \frac{x

^{{2}y}{6}z^{2}}{3c} \\&= \frac{bx

^{{2}y}{6}z^{2}}{3c} + \frac{dx^{{2}y}{6}z^{2}}{3c} \